2022
DOI: 10.1111/jerd.13000
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year randomized clinical trial to evaluate the clinical performance of high‐viscosity glass ionomer restorative systems in small class II restorations

Abstract: Objective Evaluate and compare the 5‐year clinical performance of three high‐viscosity glass ionomer restorative materials in small class II restorations. Materials and Methods Forty patients, each with four class II restorations, were enrolled in this trial. A total of 160 restorations were placed, 25% for each material, as follows: three high‐viscosity conventional glass ionomer restorative systems (Ketac Universal Aplicap, EQUIA Forte and Riva Self Cure HV) and a microhybrid resin composite system (Filtek Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 26 publications
1
35
1
1
Order By: Relevance
“…There were no radiographic indications of secondary caries or significant gaps between the base materials and gingival dentin during the evaluation periods. The use of an acidic pre‐conditioner in GI‐based base materials may enhance the chemical adhesion between GI and dentin, which may contribute to a good marginal seal and a reduced incidence of secondary caries 46,47 . In contrast, the use of an adhesive containing 10‐MDP to bond both flowable bulk fill and ion‐releasing base materials, combined with their high flow rate, may lead to good marginal integrity and a reduced risk of secondary caries 48,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no radiographic indications of secondary caries or significant gaps between the base materials and gingival dentin during the evaluation periods. The use of an acidic pre‐conditioner in GI‐based base materials may enhance the chemical adhesion between GI and dentin, which may contribute to a good marginal seal and a reduced incidence of secondary caries 46,47 . In contrast, the use of an adhesive containing 10‐MDP to bond both flowable bulk fill and ion‐releasing base materials, combined with their high flow rate, may lead to good marginal integrity and a reduced risk of secondary caries 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of an acidic pre-conditioner in GIbased base materials may enhance the chemical adhesion between GI and dentin, which may contribute to a good marginal seal and a reduced incidence of secondary caries. 46,47 In contrast, the use of an adhesive containing 10-MDP to bond both flowable bulk fill and ionreleasing base materials, combined with their high flow rate, may lead to good marginal integrity and a reduced risk of secondary caries. 48,49 Previous studies that employed the same adhesive observed no recurrent caries during follow-ups.…”
Section: Criteriamentioning
confidence: 99%
“…After assessing all radiographs under optimal light conditions, the depth of proximal carious lesions in all cases was D3. Pulp vitality was confirmed by application of cold dry ice 29 . Dental plaque and salivary pellicle were removed from teeth surface by using pumice-water slurry and rubber cup 14 .…”
Section: Methodsmentioning
confidence: 99%
“…Six studies investigated the staining surface [ 46 51 ], but only 2 of them found statically significant results regarding staining surface and margin when GIC was compared with RC ( P <0.05) [ 47 , 48 ]. The effect was observed only in minor surface staining, which was easily removed and did not exert a detrimental effect.…”
Section: Introductionmentioning
confidence: 99%
“…One study observed that Filtek Z250 outperformed other GIC materials in terms of color match ( P <0.001). EQUIA Forte restoration’s color match was superior to that of Ketac Universal or Riva HV restorations at 5-year recall [ 47 ]. Similarly, Gurgan et al [ 49 ] observed that Gradia DP outperformed EQUIA Fil.…”
Section: Introductionmentioning
confidence: 99%